PERFORMA PRODUKSI KEBUN KELAPA SAWIT RAKYAT PADA DATARAN TINGGI - Posman HP Marpaung; Fandri Siburian; Tulus Fernando Silitonga (Universitas Quality, 2019)
The limitation of mineral land as a productive land makes some people expand oil palm cultivation to peat land in marginal class conditions (Class S3). The expansion of oil palm plantations into peatlands is accompanied by Government Regulation No. 57 of 2016 concerning Protection and Management of Peat Ecosystems. The regulation has a positive effect to protect and restore the hydrological function of peat, but also affects the management of oil palm cultivation. The limitation of peatlands also makes some people switch to using the highlands as a form of agricultural and plantation extensification. Planting oil palms in the highlands is a form of expansion of oil palm cultivation that is limited due to lack of sufficient land availability. It is necessary to carry out technical culture and cost requirements that are